2009
DOI: 10.1017/s1041610209990871
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of clinically significant depressive symptoms among elderly people in Sri Lanka: findings from a national survey

Abstract: The prevalence of depressive symptoms among Sri Lankan elderly people is higher than that reported for most Asian countries. Clinicians and caregivers need to be aware of the potential presence of depressive symptoms among the elderly, especially among those with lower educational levels, functional limitations, hearing difficulty, physical disability, perceived income inadequacy, and among those who live alone, and ethnic minority males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
90
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(106 citation statements)
references
References 40 publications
(145 reference statements)
10
90
3
3
Order By: Relevance
“…In Brazil and Sri Lankan study, 14,17 low income was associated with depression, but in our study, we did not find such an association; the probable reasons could be that 90.3 % of our population were from low socioeconomic status which was distributed equally among depressed and not depressed individuals.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…In Brazil and Sri Lankan study, 14,17 low income was associated with depression, but in our study, we did not find such an association; the probable reasons could be that 90.3 % of our population were from low socioeconomic status which was distributed equally among depressed and not depressed individuals.…”
Section: Discussioncontrasting
confidence: 82%
“…However it was lower than Mumbai study carried out in an urban slum population (45.9 % 10 ). Studies from other developing countries report rates ranging from: 5.22 to 45.9 % [13][14][15][16][17][18][19] . Nevertheless, it indicates that there is considerable morbidity due to depression among elderly in India.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study covering nine European countries the prevalence of depressive symptoms varies from country to country: the lowest prevalence was in Iceland (8.8%), while the highest was in Germany (45.9%) [14]. Another study from Sri Lankans the prevalence of depressive symptoms was observed as 27.8% [15]. In Turkey; the prevalence of depressive symptoms was reported as; 27.9% in Malatya, 58.3% in Erzurum, 61.1% in Erzincan [16][17][18].…”
Section: Discussionmentioning
confidence: 99%